Penerapan Metode Forecasting Dalam Menentukan Persediaan Kopi Susu Pada Usaha Mikro Kecil Menengah Dalam Hal Ini Sir Coffeehouse Bekasi - Anisah Anisah; Hadita Hadita (Journal of Management and Creative Business, 2024)
By using mathematical calculations, a situation can be predicted in the future through forecasting or forecasting. Companies often use this forecasting method to calculate future conditions, or to make predictions or predict future conditions that are still unknown for the company's progress. Forecasting can be implemented in various ways. Two methods are used in one example: double exponential smoothing and weighted moving average (WMA). This technique provides future forecasts by dissecting past information and applying different weights to the remaining information. Predicted proportions can also be used to improve quality of life. When a problem arises, it is almost impossible to solve or understand without first recognizing the problem. This forecasting method can be used in various fields, including forecasting at coffee shops or Sir Coffeehouse coffee shops regarding the production of milk coffee drinks. Sir Coffeehouse is a coffee shop or coffee shop that sells various kinds of coffee drinks. Until now, sales and data processing for Sir Coffeehouse Coffee Shop is still manual, which of course results in less efficient management. Because salespeople often have difficulty predicting how many products will be available in the coming month, the number of sales transactions will affect inventory. Of course, by obtaining forecasting data for future coffee drinks, it can provide an overview of future work steps and boost company productivity. In this research, taking coffee milk drink stamps for the manual prediction estimation process, of course, must dominate abilities, especially in the numerical field. The test results of the system created were used to predict coffee sales with a Weighted Moving Average (WMA) of 62 and a Mean Square Error (MSE) of 0.08, while using Double Exponential Smoothing of 51.1 and a Mean Square Error of -38.0. This strategy provides stock determination for the following time period. The Weighted Moving Average (WMA) technique is superior because it has a lower error value.